PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK JAKARTA - Susilowati Susilowati; Sparta Sparta (Ibs Press, 2024)
The purpose of this study was to the Effect of Cash Turnover, Accounts Receivable Turnover and Inventory Turnover on Profitability of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange (Period 2016 – 2020). The data used in this paper were obtained from financial report data published by IDX, which was taken from the website www.idx.co.id. The theoretical basis used is signal theory. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2016 – 2020. The sampling technique used the purposive sampling method, so there were 41 companies as a sample. The data is processed using the Eviews v.10 application. Hypothesis testing using partial test (t statistical test). The results showed that Cash Turnover, Accounts Receivable Turnover, Inventory Turnover, Firm Size and Leverage had a positive effect on Profitability and simultaneously had a positive effect on Profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2020.